2019
DOI: 10.1097/md.0000000000017002
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Medicine Versus Placebo for the Treatment Of Chronic Obstructive Pulmonary Disease

Abstract: Background:Chinese herbal medicine (CHM) has been shown to be effective in the treatment of stable chronic obstructive pulmonary disease (COPD) by published meta-analyses. However, disease outcomes were inconsistent and heterogeneity was observed attributed to placebo-controlled studies. We present a protocol for a systematic review aiming to evaluate the clinical efficacy and safety of CHM comparing to placebo in the treatment of stable COPD, to provide robust evidence for the use of CHM in COPD.Methods:We wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…TNF-α is a pro-inflammatory cytokine that induces the production of other inflammatory mediators, which is elevated in AECOPD and linked with the airway inflammation and the oxidative stress[ 22 ]; (3) Change in the level of CRP in the sputum from baseline to the end of treatment, as measured using the immunoturbidimetric method (model: AU5800, Beckman Coulter, Inc., United States). CRP in sputum reflects local inflammation in the airways, which is increased in AECOPD and is associated with bacterial infection and sputum characteristics[ 23 ]; (4) The change in the IL-6 and TNF-α levels in sputum from baseline to the end of treatment, as measured using the ELISA method (R&D Systems, Inc., United States); and (5) The change in lung ventilation function parameters from baseline to the end of treatment, including FEV1, FVC, and peak expiratory flow (PEF), were measured using a spirometer (model: SP-10, Contec Medical Systems Co., Ltd., China), according to the American Thoracic Society/European Respiratory Society guidelines[ 24 ]. The participants were instructed to perform three maneuvers and the best values were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…TNF-α is a pro-inflammatory cytokine that induces the production of other inflammatory mediators, which is elevated in AECOPD and linked with the airway inflammation and the oxidative stress[ 22 ]; (3) Change in the level of CRP in the sputum from baseline to the end of treatment, as measured using the immunoturbidimetric method (model: AU5800, Beckman Coulter, Inc., United States). CRP in sputum reflects local inflammation in the airways, which is increased in AECOPD and is associated with bacterial infection and sputum characteristics[ 23 ]; (4) The change in the IL-6 and TNF-α levels in sputum from baseline to the end of treatment, as measured using the ELISA method (R&D Systems, Inc., United States); and (5) The change in lung ventilation function parameters from baseline to the end of treatment, including FEV1, FVC, and peak expiratory flow (PEF), were measured using a spirometer (model: SP-10, Contec Medical Systems Co., Ltd., China), according to the American Thoracic Society/European Respiratory Society guidelines[ 24 ]. The participants were instructed to perform three maneuvers and the best values were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…As table 1 shown, there were no statistically significant differences in age, gender, and disease period (P>0.05) in two groups, and the basal features were comparable. symptom in the TCM syndrome score system [24][25][26][27]. A score of 4 or more was set for diagnosis, a score above 4 and below 8 indicated a mild syndrome, that above 8 and below 12 indicated a moderate type, and that greater than or equal to 12 implied a severe type.…”
Section: Clinical Features Of Patientsmentioning
confidence: 99%
“…[6][7][8] Existing evidence method of traditional Chinese medicine in the treatment of COPD has gained rich experience, and combining traditional Chinese and western medicine treatment can further improve the prognosis of patients. [9,10] Traditional Chinese medicine injections (TCMIs) treating COPD at present mainly include Tanreqing injection (TRQI), Danhong injection (DHI), Xuebiqing injection (XBQI), Shenmai injection (SMI), Huangqi injection (HQI), etc. [11] Studies have confirmed that XBQI can regulate the levels of SP-D and CCL18 in patients with COPD and alleviate the clinical symptoms of patients.…”
Section: Introductionmentioning
confidence: 99%